Pelatihan Bahasa Jerman Tingkat B1 bagi guru Bahasa Jerman IGBJI Cabang Makassar - Muddin Muddin; Syamsu Rijal; Burhanuddin Burhanuddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Level B1-German Language Training for IGBJI (Association of German Language Teachers in Makassar). The training aims to provide German Language Teachers with knowledge and understanding of Gemeinsamer europäischer Referenzrahmen für Sprachen as a foothold in international level  mastery and German language test models at level B1. This training is very important to be carried out because the teacher as instructor must know about how the German language test models in B1 level so that they can inform their students. The subjects in this study were German language teachers who were members of the Makassar Branch of the German Language Teachers Association (IGBJI). The training was held from 6 July to 20 July 2019 with the implementation methods namely counseling, training, discussion and simulation. The German language training level B1 for German language teachers was carried out as planned and the results achieved in the community partnership program activities could be categorized as quite adequate. Community service activities are categorized as more than sufficient (70%) because they are judged by the activity of participants participating in the presentation of generally motivated material.